Layer-by-layer deposition of praseodymium oxide on tin-doped indium oxide (ITO) surface - Shrestha, S; Yeung, C; Marken, F; Mills, C; Tsang, S (2007)
Praseodymium oxide as a thin film of controllable layer is known to display many unique physiochemical properties, which can be useful to ceramic, semiconductive and sensor industries. Here in this short paper, we describe a new chemical method of depositing praseodymium oxide on tin-doped indium oxide (ITO) surface using a layer-by-layer approach. The process is carried out by dipping the ITO in solutions of adsorbable polycationic chitosan and alkaline praseodymium hydroxide Pr(OH) 3 alternatively in order to build up the well-defined multi-layers. XRD suggests that the predominant form of the oxide is Pr 6O 11, obtained after heat treatment of the deposited ITO in static air at 500 °C. Microscopic studies including AFM, TEM and SEM indicate that the deposited oxide particles are uniform in size and shape (cylindrical), mesoporous and the thickness of the film can be controlled. AC impedance measurements of the deposited materials also reveal that the oxide layers display a high electrical conductivity hence suitable for sensor uses. © 2006 Elsevier B.V. All rights reserved.